Penerapan Teknologi Pengering Terowongan Hohenheim Aceh pada Kelompok Wirausaha Adee Thoe Ajee - Rita Khathir; Sri Maryati; Marai Rahmawati (Institut Pertanian Bogor, 2025)
The business of processing simplicia and dried spices has challenged prospects to be developed in Aceh. Simplicia can be used as herbal medicine while dried spices are always needed in various daily cooking recipes by the community. This community service aimed to build a business for a group of young women in Ajee Cut Village, Ingin Jaya District, Aceh Besar Regency, named UKM Adee Thoe Ajee (UKM ATA) for producing simplicia and dried spices with the application of solar tunnel dryer type Hohenheim Aceh. The methods applied were focus group discussion, preparation, field school, dissemination, and ongoing assistance. The outcomes of the program were 1 unit of Hohenheim Aceh tunnel dryer, 1 unit of Android thermal printer, 1 unit of grinder at capacity of 500g, 1 package of production facilities, and raw materials for production. About 2 trainings were conducted including digital business management training, and production management training with the application of technology which were held in form of field school and dissemination. Those activities have also been published on YouTube channel of university (https://www.youtube.com/watch?v=sGmw-XMhjII&t=51) as well as through daily newspaper Serambi Indonesia in both offline and online version on 23 December, 2024 (https://aceh.tribunnews.com/2024/12/23/usk-bantu-ukm-ata-mesin-pengeringan). The products produced by UKM ATA were simplicia, and various powders of ginger, curcuma and red chili. Mentoring is carried out during the program and evaluation is carried out through the Qasir application. It is expected that by adapting production technology UKM ATA could produce at good quality as well as meet halal requirement.